(untitled) (Sebha University Conference Proceedings, 2025)
This paper describes the impact of two main issues while designing Internet of Things (IoT)-based systems for agriculture and smart farms. The first issue is the network infrastructure, which needs careful evaluation in order to meet performance and data transfer requirements. The second issue is protection from cyber security attacks. However, the paper analyzed the ZigBee based on the IEEE 802.15.4 protocol, which showed promising throughput results. The distributed denial of service attacks were modeled and simulated, but the results showed that more protection techniques need to be researched and applied for designing novel IoT-based systems while enhance reliability, embed security and improve availability in the technology applied on agriculture smart farming fields.